Cfd and analytical analysis of exhaust system of a gas turbine used in a ship - Bayraktar, Seyfeffin; Safa, Aykut; Yilmaz, Tamer (AMER INST PHYSICS, 2007)
In this study, exhaust system of the gas turbine of a ship with CODOG (Combined Diesel Or Gas-turbine) system is analyzed both analytically and numerically. The results obtained from these two different methods are then compared. The flow and heat transfer analysis of the exhaust system is done using a full scale two-dimensional (2-D) model and in the simulation velocity vectors, pressure and temperature fields are obtained. The gas turbine exhaust system velocity is 40 m/s, especially just after the inlet. For the mathematical model, time-averaged, steady-state, mean flow equations of continuity, momentum and energy equations can be written in Cartesian tensor notation. In commercially available computational fluid dynamics (CFD) code FLUENT 6.2, the governing equations are discretized using second order upwind interpolation scheme, and the discretized equations are solved using SIMPLEC algorithm. The Standard k-epsilon turbulence model is used for the turbulence closure. The boundary layer meshes are applied for obtaining more precise results, especially in the vicinity of walls. It is shown that the CFD calculations can be applied to such a practical problem to improve analysis performance. In conclusion, velocity vectors, temperature and pressure fields and pressure losses calculated CFD and analytical calculations are compared with numerical results.
Keywords: gas turbine; exhaust system; CFD; analytical approach; Mathematics; Physics